(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This article explores the multifaceted issues surrounding minors experiencing neglect, homelessness, and deviant behaviours, including drug and alcohol abuse. It highlights the critical role of personalized approaches in prevention, considering social, biological, and psychological factors. The paper emphasizes the necessity of collaboration between law enforcement, educational institutions, medical organizations, and psychological services to rehabilitate affected minors and reintegrate them into society. Additionally, it examines the rising prevalence of adolescent substance abuse and its societal impact, the challenges of rehabilitation in correctional institutions, and the vital importance of preventive measures in fostering positive behavioural changes.